Size at sex change in the protandric hermaphrodite Patagonian blenny Eleginops maclovinus ( Cuvier , 1830) in central‐southern Chile - Andrés Flores; Rodrigo Wiff; Donald I. Brown (Journal of Fish Biology, 2026)
Hermaphroditic fish species show low resilience to fishing exploitation, as alterations in sex ratio or size at sexual transition have direct implications for population fitness. The Patagonian blenny is a protandric hermaphrodite of economic importance in Chile, where basic knowledge of its life‐history traits remains scarce. Using individuals collected from the artisanal fishery, we estimated the proportion of females at length (P F ) for this species in Chile through histological analysis, and compared our findings with those of previous studies conducted in the southeast Pacific and southwest Atlantic. A total of 301 individuals were collected during March and from July to October 2022, of which 189 gonads were submitted to histological analysis. P F was estimated using a generalised linear model with a binomial error distribution. Histological analysis indicated that females possess a group‐synchronous gonadal development, whose reproductive season occurs during autumn–winter. The sexual transitional phase occurs between 30 and 40 cm in total length (L T ). The fitted ogive of P F did not differ significantly between macroscopic and histological methods ( p > 0.05). However, temporal and spatial variations in P F were evident when compared to previous studies conducted on both the Pacific and Atlantic sides. In Chile, this study revealed a decrease in the size at sexual transition for this species from 41.6 cm L T in 1974–1975 to 35.7 cm L T in 2022, highlighting the need for a monitoring system and the implementation of appropriate management measures.